Genetic Evaluation of African Collections of Acacia senegal in Western Rajasthan - Jindal, S K; Singh, Manjit; Patel, Nisha; Pancholy, Anjly (Annals of Arid Zone, 2016)
Acacia senegal, a multipurpose tree, grows well on poor sandy soils of arid areas. Seeds of five accessions collected from the forests of Niger, Mali and Senegal were procured from CIFT France to identify suitable accessions for arid areas of India and plants for better survival and more biomass. The trial was established in 1988 with a spacing of 3 m x 3 m at Jodhpur. Average rainfall during the trial was 375.9 mm ranging between 50.6 mm (2002) and 844.0 mm (1990). Data were recorded in December of 2001 to 2005. Grand mean survival was 34.4% at 13-year age. EC 87/7493, an accession collected from ATE Nord Quest AOUROU Mali showed maximum survival, tree height, collar diameter, dbh and canopy diameter for all the growth stages. Heritability was more than 70% for tree hei?ht. Variation was maximum due to residual factors for all the traits. Key words: Acacia senegal, exotic material, evaluation, genetic components.